A Model of In vitro Plasticity at the Parallel Fiber—Molecular Layer Interneuron Synapses - Lennon, William; Yamazaki, Tadashi; Hecht-Nielsen, Robert (Frontiers in Computational Neuroscience, 2015)
Theoretical and computational models of the cerebellum typically focus on the role of parallel fiber (PF) - Purkinje cell (PKJ) synapses for learned behavior, but few emphasize the role of the molecular layer interneurons (MLIs) -- the stellate and basket cells. A number of recent experimental results suggest the role of MLIs is more important than previous models put forth. We investigate learning at PF - MLI synapses and propose a mathematical model to describe plasticity at this synapse. We perform computer simulations with this form of learning using a spiking neuron model of the MLI and show that it reproduces six in vitro experimental results in addition to simulating four novel protocols. Further, we show how this plasticity model can predict the results of other experimental protocols that are not simulated. Finally, we hypothesize what the biological mechanisms are for changes in synaptic efficacy that embody the phenomenological model proposed here.